The Effects of Short Selling Bans on the Stock Price Volatility of LQ45 Banking Companies in Indonesia - Mustapha Bayu Firdaush; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2025)
The COVID-19 pandemic has significantly impacted the stability of Indonesia's financial markets. The ensuing economic recession has led to high volatility in the stock market, particularly for banking stocks included in the LQ45 index. One of the policy implemented by regulator to mitigate market volatility was a wide ban on short selling. This study aims to analyze the impact of the short selling ban imposed by the Indonesian Stock Exchange in March 2020 on the volatility of LQ45-indexed banking stocks in Indonesia during the COVID-19 pandemic. Secondary data will be used, and the analysis will employ a panel data regression method. The results of this study indicate that the short selling bans had a statistically significant positive effect on the volatility of LQ45-indexed banking stocks in Indonesia.